Des vestiges d’un possible aqueduc à Lyon, à l’angle des rues Appian et des Fossés-de-Trion - Tony Silvino (Gallia)
A building operation at the intersection of the Appian and Fossés-de-Trion streets, in Lyon’s fifth district (France), gave rise to an archaeological excavation in 2015. The site is located near the Point-du-Jour plain, close to the Saint-Irénée district, in the southern ridge of the Trion valley, with the Fourvière hill to the north-east and the plain of Sainte-Foy to the south-west. In ancient times, the site was located in the south-western suburbium of the colony of Lugdunum, a space occupied by a series of different activities, with housing, agricultural areas, areas with craft or commercial activities and even a necropolis. The suburbium was structured by the Aquitaine Roman road and the four aqueducts that supplied water to the colony and that converged in this zone.The excavation uncovered two parallel structures dug into the natural substrate, with a south-south-west and north-north-east orientation. The first structure is 4.20 m wide at the base and is visible for 6.5 m. It disappears to the south, though it becomes visible again in the northern section of the excavation. Its profile is flat at the base with sides that slope outwards to widen at the top. The preserved entity measures about 0.50 m. The second structure is located 2.20 m to the west of the first. It also has a relatively flat bottom and very sloping sides. The preserved area is around 5.40 m long and 2.80 m wide at the base. The largest preserved section is about 0.44 m deep. It runs through the whole site over a distance of 24 m. The interior of the structures is relatively rich, material-wise, with a large quantity of earthenware pipe fragments. The exact timeframe of the structures is difficult to ascertain, though a study of the materials found inside tells us when they were last used. The ceramics found suggests that the structures were abandoned during the Augustan period, probably in the last phase, i.e. the beginning of the common era.The orientation and destination of these structures are anomalous, particularly the longest of the two. It does not seem likely that they had a drainage function, given their topographical location, their profiles and the absence of soil preparation, as geomorphological analysis has demonstrated. At the same time, these structures do not appear to be roads, for example connecting the Trion valley in the north-west to Point-du-Jour plateau in the south-east, since there are no signs of hardtop preparation at the bottom of the structures. Finally, both of them appear to have been closed very quickly.The remnants that have provided the most information for the interpretation of the structures are the ones found within them, more specifically the fragments of earthenware pipe. There are several scenarios under which these fragments might have ended up on the bottom of the structures. The pipes could be rejected items from a nearby production area. They could have been used to drain rainwater or sewage. They could also have been used to transport clean water. It is possible that these earthenware objects had a public function, supplying water to the Lugdunum area. Not much is known about the Roman city’s water supply structures for this period, though several techniques may have been employed: digging of wells, rainwater recovery and aqueduct building (Chomer 2018). With respect to the latter suggestion, the existence of aqueducts during the reign of Augustus remains a matter of debate. One of the four known aqueducts, Yzeron, might have been built within this timeframe. Part of this aqueduct has recently been found in Point-du-Jour avenue (Lyon 5th).The hypothesis that the fragments of earthenware pipe found in Appian street belonged to an aqueduct structure is reinforced by the facts already mentioned. They could be part of an early siphon, in which earthenware was used rather than lead. The pipe fragments are extremely thick, capable of resisting high water pressure. According to Vitruvius, earthenware pipes were less costly to use, though also less effective, than lead, and this were easier to repair and healthier. There are several earthenware aqueducts known throughout the Roman Empire, such as the siphon in the terminal section of the Almuñécar aqueduct, in Spain.The earthenware pipe fragments from Appian street were not found in place. Also, the placement and function of the earthworks, such as trench F112, tend to cast doubt on the hypothesis proposed above. On the other hand, if these structures were part of an aqueduct, trench F112 might simply be a possible siphon earthwork, either a mistake, a temporary trench or a pilot structure, built in advance to assess the possibility of the aqueduct.Ultimately, the hypothesis that there was an aqueduct in this area during the reign of Augustus is viable, though it should treated with caution since the traces are quite sparse. More archaeological excavations need to be carried out in remaining areas located on the predicted line to verify if there really was an aqueduct there.